Caracterização do imunofenótipo das células envolvidas no processo fibrótico de fígados bovinos cronicamente infectados por Fasciola hepatica - Sousa, Dyeime Ribeiro (2014)
The fascioliasis is a disease caused by the parasite Fasciola hepatica which can cause severe liver fibrosis. This study aimed to characterize the immunophenotype of cells involved in liver fibrogenesis of cattle with this disease. To this, 74 bovine livers condemned for fascioliasis were collected for histological processing and immunohistochemistry with anti-a-SMA, anti-elastin and anti-ER-TR7 antibodies. Was taken the classification of the degree of fibrosis followed by identification and quantification of each cell type in the parenchyma and portal space. Were used descriptive statistics and Spearman correlation test. In the right lobe of the liver 90.5% (67/74) was classified as fibrosis grade 1, 8.1% (6/74) as fibrosis grade 2 and 1.4% (01/74) as fibrosis grade 3. In the left hepatic lobe, 55.4% (41/74) of livers were classified as grade 1, 28.4% (21/74) as grade 2 and 16.2% (12/74) as grade 3. There were significant positive association (? = 0.41, p <0.0001) between the degree of fibrosis and hepatic lobe, revealing more fibrosis in the left lobe. Observed hepatic stellate cell (HSC) distributed in the parenchyma and myofibroblasts (MF) in portal spaces. No fibroblasts were found. The mean of HSC was 23.9 and there was significant correlation between the degree of fibrosis (? = -0.44, p <0.0001) and the amount of HSC (? = -0.61, p <0.0001) in the right and left lobes. The MF were found around the portal structures, venules, arterioles and biliar ducts and there was positive and significant correlation between the number of layers around each structure of the EP with the degree of fibrosis (? = 0.19, p <0.0001), though, has not been influenced by any structure of the portal space, in particular (p> 0.05). Concluded that the cells that participate in the fibrogenesis of the bovine livers with chronic fascioliasis are HSC and MF. These cells are involved in hepatic fibrogenesis because they increase in number with the progression of fibrosis